Positive electrode active material and lithium secondary battery containing the same
By introducing the concentration gradient of cobalt into the lithium composite oxide, the problem of particle stability damage during charging and discharging of lithium secondary batteries is solved, and higher battery performance and reliability are achieved.
Patent Information
- Application Number
- CN202211297852.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2021-10-26
- Filing Date
- 2022-10-21
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2042-10-21
AI Technical Summary
During the charging and discharging process of lithium secondary batteries, the volume change of lithium composite oxide leads to stress accumulation, which in turn damages particle stability and affects the performance and reliability of the battery.
The concentration gradient of cobalt is introduced into the lithium composite oxide, which decreases from the surface to the center, and the slope of the concentration gradient has different symbols and different values to improve the stability of the particles.
By introducing the concentration gradient of cobalt, the volume change and stress accumulation of lithium composite oxides during charging and discharging are alleviated, and the stability of the positive electrode active substance and the performance of lithium secondary batteries are improved.
Smart Images

Figure BDA0003901678860000251 
Figure BDA0003901678860000261 
Figure BDA0003901678860000271
Abstract
Description
Technical Field
[0001] The present invention relates to a positive electrode active material and a lithium secondary battery containing the same, and more specifically, to a positive electrode active material, a positive electrode containing the above-mentioned positive electrode active material, and a lithium secondary battery using the above-mentioned positive electrode, wherein the positive electrode active material comprises a lithium composite oxide containing at least nickel and cobalt, and the cobalt in the above-mentioned lithium composite oxide has a concentration gradient from the surface to the center, and the above-mentioned concentration gradient has at least different slopes, thereby improving the stability of the particles in the surface and center of the above-mentioned lithium composite oxide. Background Art
[0002] Batteries use materials that can undergo electrochemical reactions at the positive and negative electrodes to store electrical energy. A typical example of such batteries is a lithium secondary battery that stores electrical energy through the difference in chemical potential when lithium ions are inserted / released between the positive and negative electrodes.
[0003] The lithium secondary battery is prepared by using a substance capable of reversibly inserting and extracting lithium ions as a positive electrode active material and a negative electrode active material, and filling an organic electrolyte or a polymer electrolyte between the positive electrode and the negative electrode.
[0004] Lithium composite oxides are used as positive electrode active materials for lithium secondary batteries, and as examples thereof, composite oxides such as LiCoO2, LiMn2O4, LiNiO2, and LiMnO2 are being studied.
[0005] Among the above-mentioned positive electrode active materials, LiCoO2 is widely used due to its excellent life characteristics and charge and discharge efficiency. However, cobalt used as a raw material has limited resources and is expensive, so it has a disadvantage of limited price competitiveness.
[0006] Lithium manganese oxides such as LiMnO2 and LiMn2O4 have the advantages of excellent thermal stability and low price, but have the problems of small capacity and poor high temperature characteristics. In addition, LiNiO2 positive electrode active material shows battery characteristics of high discharge capacity, but due to the cation mixing problem between Li and transition metals, it is difficult to synthesize, thus having a big problem in rate characteristics.
[0007] In addition, depending on the severity of this cation mixing, a large amount of Li byproducts are generated, most of which are composed of LiOH and Li2CO3 compounds. When preparing positive electrode slurry, it becomes a gel problem and a cause of gas generation caused by charging and discharging after preparing the electrode. Residual Li2CO3 reduces the cycle by increasing the swelling phenomenon of the monomer and also becomes a cause of battery expansion.
[0008] In addition, when charging and discharging, the lithium composite oxide contained in the positive electrode active material changes in volume according to the insertion / extraction of lithium ions in the lithium composite oxide. Generally, the lithium composite oxide is in the form of secondary particles formed by the aggregation of multiple primary particles. When charging and discharging, when a rapid volume change of multiple primary particles occurs or stress is accumulated due to repeated charging and discharging, there is a problem of cracks in the secondary particles or collapse or change (phase change) of the crystal structure.
[0009] Such a problem eventually causes a decrease in the stability and reliability of the positive electrode active material, and therefore various studies are being conducted to alleviate the volume change of the lithium composite oxide during charge and discharge or to minimize the stress caused by the volume change to prevent particle damage. Summary of the invention
[0010] Technical issues
[0011] In the lithium secondary battery market, the growth of lithium secondary batteries for electric vehicles dominates the market. At the same time, the demand for positive electrode materials used in lithium secondary batteries is also changing.
[0012] For example, conventionally, lithium secondary batteries using LFP have been mainly used from the viewpoint of ensuring safety, but recently, the use of nickel-based lithium composite oxides having a larger energy capacity per unit weight than LFP has been expanding.
[0013] Therefore, positive electrode active materials used in lithium secondary batteries of higher specifications should satisfy the stability and reliability that are reasonably expected even under more severe operating conditions.
[0014] In the past, in order to prevent particle damage by alleviating volume changes of lithium composite oxides or minimizing stress caused by volume changes during charge and discharge, the aggregation of primary particles was reduced to allow predetermined gaps between primary particles to exist, thereby dispersing stress caused by volume changes of primary particles. However, such lithium composite oxides have a limitation of reduced energy density per unit volume.
[0015] In many such cases, the inventors have discovered that when the cobalt in a lithium composite oxide containing at least nickel and cobalt has a concentration gradient (at least with different slopes) from the surface toward the center, the stability of the particles at the surface and center of the lithium composite oxide can be improved.
[0016] Therefore, the object of the present invention is to provide a positive electrode active material comprising a lithium composite oxide containing at least nickel and cobalt, wherein the cobalt in the above-mentioned lithium composite oxide has a concentration gradient decreasing from the surface portion toward the center portion of the above-mentioned lithium composite oxide, and the above-mentioned cobalt concentration gradient has at least different slopes, and the signs of the above-mentioned different slopes are the same as each other.
[0017] Furthermore, an object of the present invention is to provide a positive electrode active material, which is a secondary particle formed by aggregation of multiple primary particles, comprising a lithium composite oxide having a coating layer covering the interface between the above-mentioned primary particles and at least a portion of the surface of the above-mentioned secondary particles, wherein the cobalt in the above-mentioned lithium composite oxide has a concentration gradient decreasing from the surface portion toward the center portion of the above-mentioned lithium composite oxide, and the above-mentioned cobalt concentration gradient has at least different slopes, and the signs of the above-mentioned different slopes are the same as each other.
[0018] Furthermore, another object of the present invention is to provide a positive electrode comprising the positive electrode active material defined in the present application.
[0019] Meanwhile, another object of the present invention is to provide a lithium secondary battery using the positive electrode defined in this application.
[0020] Solutions to the problem
[0021] According to one aspect of the present invention, a positive electrode active material is provided, which comprises a lithium composite oxide containing at least nickel and cobalt, wherein the cobalt in the above-mentioned lithium composite oxide has a concentration gradient decreasing from the surface portion toward the center portion of the above-mentioned lithium composite oxide, and the above-mentioned cobalt concentration gradient has at least different slopes.
[0022] The concentration gradient of the cobalt in the lithium composite oxide has at least different slopes, and the signs of the different slopes are the same. That is, the cobalt in the lithium composite oxide differs in the degree of concentration reduction only in the region where the different slopes exist, and the direction of concentration reduction is the same.
[0023] In one embodiment, an absolute value of a slope of the cobalt in the lithium composite oxide relative to a surface portion of the lithium composite oxide may be greater than an absolute value of a slope relative to a center portion of the lithium composite oxide.
[0024] In one embodiment, when performing energy profiling-energy dispersive X-ray spectroscopy (EP-EDS) analysis, there may be an inflection point of the change in the slope of the concentration gradient of the cobalt in the above-mentioned lithium composite oxide in the region of an accelerating voltage of 7.5 kV to 12.5 kV. In energy profiling-energy dispersive X-ray spectroscopy, for the surface of the above-mentioned lithium composite oxide, the cumulative concentration of cobalt from the surface of the above-mentioned secondary particles to the depth penetrated by the above-mentioned electron beam is measured using an electron beam irradiated with an accelerating voltage increased from 1 kV to 30 kV.
[0025] Furthermore, the lithium composite oxide may be a secondary particle formed by aggregation of a plurality of primary particles, and cobalt in the secondary particle may have a concentration gradient decreasing from a surface portion toward a center portion of the secondary particle.
[0026] At this time, when energy analysis-energy dispersive X-ray spectroscopy analysis is performed, there may be an inflection point in the change of the slope of the concentration gradient of cobalt in the above-mentioned secondary particles in the region of acceleration voltage of 7.5kV to 12.5kV. In the energy analysis-energy dispersive X-ray spectroscopy, for the surface of the above-mentioned secondary particles, the cumulative concentration of the above-mentioned cobalt from the surface of the above-mentioned secondary particles to the depth penetrated by the above-mentioned electron beam is measured using an electron beam irradiated with an acceleration voltage increased from 1kV to 30kV.
[0027] In one embodiment, when the slope of the concentration gradient of the cobalt in the lithium composite oxide in the acceleration voltage range of 1 kV to 10 kV is set to s1, s1 may satisfy the following formula 1.
[0028] Formula 1: 2.0≤s1≤3.6
[0029] Furthermore, when the slope of the concentration gradient of the cobalt in the lithium composite oxide in the acceleration voltage region of 10 kV to 30 kV is set to s2, s2 may satisfy the following formula 2.
[0030] Formula 2: 0.2≤s2≤0.7
[0031] Preferably, when the slope of the cobalt concentration gradient in the lithium composite oxide in the region of acceleration voltage of 1 kV to 10 kV is set to s1 and the slope of the cobalt concentration gradient in the lithium composite oxide in the region of acceleration voltage of 10 kV to 30 kV is set to s2, s1 and s2 may satisfy the following formula 3.
[0032] Formula 3: 1.7≤s1-s2≤3.0
[0033] In one embodiment, the lithium composite oxide can be represented by the following Chemical Formula 1.
[0034] Chemical formula 1: Li w Ni 1-(x+y+z+z') Co x M1 y M2 z B z' O2
[0035] (Wherein, M1 is at least one selected from Mn and Al, M2 is at least one selected from P, Sr, Ba, Ti, Zr, Mn, Al, W, Ce, Hf, Ta, Cr, F, Mg, Cr, V, Fe, Zn, Si, Y, Ga, Sn, Mo, Ge, Nd, Gd and Cu, M1 and M2 are different from each other, 0.5≤w≤1.5, 0≤x≤0.50, 0≤y≤0.20, 0≤z≤0.20, 0≤z'≤0.20.)
[0036] The lithium composite oxide may further include a coating layer covering at least a portion of the interface between the primary particles and the surface of the secondary particles. In this case, at least one metal oxide represented by the following Chemical Formula 2 may exist in the coating layer.
[0037] Chemical formula 2: Li a M3 b O c
[0038] (Wherein, M3 is at least one selected from Ni, Mn, Co, Fe, Cu, Nb, Mo, Ti, Al, Cr, Zr, Zn, Na, K, Ca, Mg, Pt, Au, B, P, Eu, Sm, W, Ce, V, Ba, Ta, Sn, Hf, Ce, Gd and Nd, 0≤a≤10, 0≤b≤8, 2≤c≤13, but the case where a and b are both 0 is excluded.)
[0039] Furthermore, according to still another aspect of the present invention, there is provided a positive electrode comprising the positive electrode active material defined in the present application.
[0040] Meanwhile, according to another aspect of the present invention, a lithium secondary battery using the positive electrode defined in the present application is provided.
[0041] Effects of the Invention
[0042] As mentioned above, when charging and discharging, the lithium composite oxide contained in the positive electrode active material is inevitably accompanied by volume changes according to the insertion / extraction of lithium ions in the lithium composite oxide. At this time, there are multiple solutions to alleviate the volume change of the lithium composite oxide during charging and discharging or minimize the stress generated according to the volume change to prevent damage to the particles, but it cannot be regarded as a sufficient solution to the deterioration problem of lithium secondary batteries caused by damage to the lithium composite oxide contained in the positive electrode active material.
[0043] However, according to the present invention, in a lithium composite oxide containing at least nickel and cobalt, when the cobalt in the above-mentioned lithium composite oxide has a concentration gradient that decreases from the surface portion toward the center portion of the above-mentioned lithium composite oxide and the above-mentioned cobalt concentration gradient has at least different slopes with the same sign as each other, even if charging and discharging are repeated, problems such as the generation of cracks in secondary particles, collapse of the crystal structure or change (phase change) of the crystal structure can be improved.
[0044] Therefore, when the positive electrode active material of the present invention is used, the performance degradation of the lithium secondary battery caused by the positive electrode active material can be alleviated.
[0045] In addition to the effects described above, specific effects of the present invention will be described together with specific embodiments of the present invention described below. DETAILED DESCRIPTION
[0046] Hereinafter, the positive electrode active material of the present invention and the lithium secondary battery including the positive electrode active material will be described in more detail.
[0047] Positive active material
[0048] According to one aspect of the present invention, a positive electrode active material is provided, which includes a lithium composite oxide containing at least nickel and cobalt. In addition to nickel and cobalt, the lithium composite oxide contains lithium and is a composite metal oxide capable of inserting and extracting lithium ions.
[0049] The cobalt in the above-mentioned lithium composite oxide may have a concentration gradient that decreases from the surface portion toward the center portion of the above-mentioned lithium composite oxide. The concentration of the transition metal in the above-mentioned lithium composite oxide can be measured by various well-known methods. For example, after the above-mentioned lithium composite oxide is cross-sectioned, the concentration of the target transition metal is analyzed by EDS mapping and line scanning. In this case, the concentration change of the target transition metal can be confirmed from the surface portion toward the center portion of the above-mentioned lithium composite oxide. In addition, there is the following energy analysis-energy dispersive X-ray spectroscopy (Energy Profiling-Energy Dispersive X-ray Spectroscopy, EP-EDS) method: by changing the acceleration voltage (V acc ), and measuring the concentration of the target transition metal accumulated from the surface of the above-mentioned lithium composite oxide to a specific depth penetrated by the electron beam at each accelerating voltage.
[0050] In the present application, the concentration of transition metals is analyzed by the aforementioned energy analysis-energy dispersive X-ray spectroscopy method. Specifically, when the energy analysis-energy dispersive X-ray spectroscopy is performed, the above-mentioned lithium composite oxide shows a concentration gradient in which the concentration of cobalt decreases from the surface portion toward the center portion. In the energy analysis-energy dispersive X-ray spectroscopy, for the surface of the above-mentioned lithium composite oxide of the present application, the cumulative concentration of cobalt from the surface of the above-mentioned secondary particle to the depth penetrated by the above-mentioned electron beam is measured using an electron beam irradiated with an accelerating voltage increased from 1 kV to 30 kV.
[0051] For example, when the electron beam can penetrate from the surface of the lithium composite oxide to a depth of about 300 nm by irradiating the surface of the lithium composite oxide with an electron beam having an accelerating voltage of 10 kV, the concentration of the target transition metal present in the region from the surface of the lithium composite oxide to a depth of 300 nm can be measured by the energy analysis-energy dispersive X-ray spectrometry. Also, when the electron beam can penetrate from the surface of the lithium composite oxide to a depth of about 800 nm by irradiating the surface of the lithium composite oxide with an accelerating voltage of 20 kV, the concentration of the target transition metal present in the region from the surface of the lithium composite oxide to a depth of 800 nm can be measured by the energy analysis-energy dispersive X-ray spectrometry.
[0052] That is, it can be interpreted that when the measured cumulative concentration of the target transition metal decreases with increasing acceleration voltage of the electron beam irradiating the surface of the lithium composite oxide, the concentration of the target transition metal has a gradient decreasing from the surface portion toward the center portion of the lithium composite oxide.
[0053] In this case, the cobalt concentration gradient may be a concentration gradient in which the cobalt concentration in the lithium composite oxide decreases continuously or discontinuously from the surface portion toward the center portion.
[0054] That is, when the concentration of cobalt decreases from the start point to the end point of any interval in which the concentration of cobalt is measured, the cobalt may be said to have a concentration gradient that decreases from the start point toward the end point of the arbitrary interval.
[0055] Furthermore, the concentration gradient of the cobalt in the lithium composite oxide may have at least different slopes. That is, there may be a plurality of concentration gradient regions having different slopes from the surface toward the center of the lithium composite oxide.
[0056] At this time, the different slopes shown by the above-mentioned cobalt concentration gradient in the above-mentioned lithium composite oxide refer to different slopes with significant differences. That is, the above-mentioned different slopes show differences outside the error range, preferably, different slopes showing a difference of more than 2 times, and more preferably, different slopes showing a difference of more than 3 times. For example, when any one of the above-mentioned different slopes has a slope of ×, when the other slope preferably has a slope of 2× or more, more preferably has a slope of 3× or more, it can be regarded as having a different slope defined in the present application.
[0057] When the outermost concentration gradient interval closest to the above-mentioned lithium composite oxide is set as the first concentration gradient interval and the concentration gradient interval existing inside the above-mentioned first concentration gradient interval is set as the second concentration gradient interval, the slope of the above-mentioned cobalt concentration gradient in the above-mentioned first concentration gradient interval and the slope of the above-mentioned cobalt concentration gradient in the above-mentioned second concentration gradient interval are independent of each other and may have the same sign.
[0058] In addition, when analyzing the concentration of transition metals in the above-mentioned lithium composite oxide by the aforementioned energy analysis-energy dispersive X-ray spectroscopy method, the absolute value of the slope of the above-mentioned cobalt in the above-mentioned lithium composite oxide relatively close to the surface of the above-mentioned lithium composite oxide may be greater than the absolute value of the slope relatively close to the center of the above-mentioned lithium composite oxide.
[0059] According to the above example, the absolute value of the slope of the cobalt concentration gradient in the first concentration gradient range may be greater than the absolute value of the slope of the cobalt concentration gradient in the second concentration gradient range.
[0060] That is, the cobalt concentration decreases more significantly in a region relatively close to the surface of the lithium composite oxide, and the cobalt concentration decreases less significantly in a region relatively close to the center of the lithium composite oxide.
[0061] As described above, from the surface portion toward the center portion of the lithium composite oxide, the first concentration gradient interval and the second concentration gradient interval in which the absolute values of the slope of the cobalt concentration gradient are different are formed, thereby improving the particle stability in the surface portion of the lithium composite oxide where the insertion / deinsertion of lithium ions is more concentrated, and alleviating the drop in the cobalt in the second concentration gradient interval, thereby improving the particle stability in the surface portion and the center portion of the lithium composite oxide.
[0062] Specifically, when energy analysis-energy dispersive X-ray spectroscopy is performed, an inflection point of the change in the slope of the concentration gradient of cobalt in the above-mentioned lithium composite oxide may exist in the region of acceleration voltage of 7.5kV to 12.5kV. In the energy analysis-energy dispersive X-ray spectroscopy, for the surface of the above-mentioned lithium composite oxide, the cumulative concentration of the above-mentioned cobalt from the surface of the above-mentioned secondary particles to the depth penetrated by the above-mentioned electron beam is measured using an electron beam irradiated with an acceleration voltage increased from 1kV to 30kV.
[0063] The inflection point refers to the position where the first concentration gradient interval is transformed into the second concentration gradient interval.
[0064] When the inflection point defined under the premise that the total amount of cobalt in the above-mentioned lithium composite oxide is the same exists at a position where the acceleration voltage is less than 7.5 kV, the position where the above-mentioned first concentration gradient interval is converted into the above-mentioned second concentration gradient interval is too close to the outermost periphery of the above-mentioned lithium composite oxide, and it is difficult to fully prevent particle damage such as cracks, collapse of the crystal structure or changes in the crystal structure (phase transition) on the inner side of the above-mentioned lithium composite oxide.
[0065] On the contrary, when the inflection point defined above exists at a position where the acceleration voltage is greater than 12.5 kV under the premise that the total amount of cobalt in the above-mentioned lithium composite oxide is the same, as the position where the above-mentioned first concentration gradient interval is converted into the above-mentioned second concentration gradient interval is excessively far away from the outermost periphery of the above-mentioned lithium composite oxide, it is difficult to fully prevent particle damage such as cracks in the surface portion of the above-mentioned lithium composite oxide, collapse of the crystal structure or changes in the crystal structure (phase transition).
[0066] The lithium composite oxide defined in the present application may be represented by Chemical Formula 1 below.
[0067] Chemical formula 1: Li w Ni 1-(x+y+z+z') Co x M1 y M2 z B z' O2
[0068] (Wherein, M1 is at least one selected from Mn and Al, M2 is at least one selected from P, Sr, Ba, Ti, Zr, Mn, Al, W, Ce, Hf, Ta, Cr, F, Mg, Cr, V, Fe, Zn, Si, Y, Ga, Sn, Mo, Ge, Nd, Gd and Cu, M1 and M2 are different from each other, 0.5≤w≤1.5, 0≤x≤0.50, 0≤y≤0.20, 0≤z≤0.20, 0≤z'≤0.20.)
[0069] The lithium composite oxide may be a high-Ni type lithium composite oxide in which the concentrations (molar percentage) of Ni, Co, M1, M2, and B in the chemical formula 1 satisfy the following relational formula 1.
[0070] Relationship 1: Ni / (Ni+Co+M1+M2+B)≥80.0
[0071] Furthermore, the above-mentioned lithium composite oxide can be the following lithium composite oxide: in the above-mentioned chemical formula 1, the concentrations (molar percentage) of Ni, Co, M1, M2 and B satisfy the above-mentioned relationship 1, and at the same time, the Co content is less than 10 molar percent, preferably less than 5 molar percent of a high-Ni / low-Co (low-Co) type lithium composite oxide.
[0072] That is, in the lithium composite oxide, the concentrations (molar percentage) of Ni, Co, M1, M2, and B in the chemical formula 1 may satisfy the following relational formula 2.
[0073] Relationship 2: Co / (Ni+Co+M1+M2+B)≤5.0
[0074] Generally, it is known that in a lithium composite oxide containing at least nickel and cobalt, as the content of Ni increases, structural instability of the lithium composite oxide caused by Li / Ni cation mixing may occur. In addition, it is reported that in a lithium composite oxide containing at least Ni and Co, as the content of Co decreases, the initial overvoltage (resistance) increases, thereby inevitably reducing efficiency characteristics.
[0075] However, the lithium composite oxide contained in the positive electrode active material according to one embodiment of the present invention has a concentration gradient in which the concentration of cobalt decreases while showing at least a different slope from the surface portion toward the center portion of the above-mentioned lithium composite oxide, which can alleviate and / or prevent the structural instability and reduction of efficiency characteristics of high-Ni or high-Ni / low-Co lithium composite oxides.
[0076] In addition, the lithium composite oxide contained in the positive electrode active material defined in the present application may be a secondary particle including at least one type of primary particle.
[0077] Here, "secondary particles comprising at least one type of primary particles" should be interpreted as including both "particles formed by the aggregation of multiple primary particles" and "particles comprising a single primary particle in a non-aggregated form".
[0078] The primary particles and the secondary particles may each independently have a rod-like, elliptical and / or irregular shape.
[0079] When the average major axis length is used as an index showing the size of the primary particles and the secondary particles, the average major axis length of the primary particles constituting the lithium composite oxide may be 0.1 μm to 5 μm, and the average major axis length of the secondary particles may be 1 μm to 30 μm. The average major axis length of the secondary particles may vary depending on the number of the primary particles constituting the secondary particles, and the positive electrode active material may include particles having various average major axis lengths.
[0080] In the case where the above-mentioned lithium composite oxide is "particles in a non-aggregated form containing a single primary particle" or "particles formed by aggregation of a smaller number of primary particles", the size (average particle size) of the primary particles contained in the "particles in a non-aggregated form containing a single primary particle" or "particles formed by aggregation of a smaller number of primary particles" may be larger than the size (average particle size) of the primary particles contained in the "secondary particles formed by aggregation of tens to hundreds or more primary particles".
[0081] As described above, compared to the case of preparing "secondary particles formed by the aggregation of tens to hundreds or more primary particles", the lithium composite oxide as "particles in a non-aggregated form containing a single primary particle" or "particles formed by the aggregation of a small number of primary particles" requires strong heat treatment conditions (high heat treatment temperature / long heat treatment). Generally, when heat treatment is performed for a long time at a temperature close to 1000°C, particle growth (crystal growth) is promoted, thereby obtaining a positive electrode active material with a reduced degree of aggregation of particles while increasing the size of a single particle.
[0082] For example, when the lithium composite oxide is a "non-aggregated particle including a single primary particle" or a "particle formed by a small number of primary particles aggregated", the average major axis length of the primary particles may be in the range of 0.5 μm to 20 μm. On the contrary, when the lithium composite oxide is a "particle formed by a plurality of (tens to hundreds or more) primary particles aggregated", the average major axis length of the primary particles may be in the range of 0.1 μm to 5 μm.
[0083] Furthermore, the primary particles may include at least one type of crystallite. That is, the primary particles may be composed of a single crystallite or may exist as particles including a plurality of crystallites.
[0084] In one embodiment, the lithium composite oxide is a secondary particle formed by aggregation of a plurality of primary particles, and cobalt in the secondary particle may have a concentration gradient decreasing from a surface portion toward a center portion of the secondary particle.
[0085] In this case, the cobalt concentration gradient formed in the secondary particles has at least different slopes, and the different slopes have the same signs.
[0086] Furthermore, when energy analysis-energy dispersive X-ray spectroscopy is performed, there may be an inflection point in the change of the slope of the concentration gradient of cobalt in the above-mentioned secondary particles in the region of accelerating voltage of 7.5 kV to 12.5 kV. In the energy analysis-energy dispersive X-ray spectroscopy, for the surface of the above-mentioned secondary particles, the cumulative concentration of the above-mentioned cobalt from the surface of the above-mentioned secondary particles to the depth penetrated by the above-mentioned electron beam is measured using an electron beam irradiated with an accelerating voltage increased from 1 kV to 30 kV.
[0087] As mentioned above, the inflection point may refer to a position where the first concentration gradient range in the secondary particle is transformed into the second concentration gradient range.
[0088] At this time, the position of the inflection point can be determined as the position where the slope of the cobalt concentration gradient in the secondary particles changes rapidly, and can also be determined as the position where any acceleration voltage penetrates when performing energy analysis-energy dispersive X-ray spectroscopy.
[0089] For example, the region where the acceleration voltage is 1 kV to 10 kV is defined as the first concentration gradient interval, and the slope of the concentration gradient of the cobalt in the lithium composite oxide in the first concentration gradient interval can be set to s1. In addition, the region where the acceleration voltage is 10 kV to 30 kV is defined as the second concentration gradient interval, and the slope of the concentration gradient of the cobalt in the lithium composite oxide in the second concentration gradient interval can be set to s2. Of course, there may be additional concentration gradient intervals inside the second concentration gradient interval, but the particle stability of the lithium composite oxide expected in the present application can be fully improved by the slope of the concentration gradient of the cobalt in the first concentration gradient interval and the slope of the concentration gradient of the cobalt in the second concentration gradient interval.
[0090] The slope s1 of the concentration gradient of the cobalt in the lithium composite oxide in the first concentration gradient region may satisfy the following formula 1.
[0091] Formula 1: 2.0≤s1≤3.6
[0092] Under the premise that the total amount of cobalt in the lithium composite oxide is the same, the slope s1 of the concentration gradient in the first concentration gradient interval is greater than 3.6, which may mean that the position where the first concentration gradient interval is converted into the second concentration gradient interval is too close to the outermost periphery of the lithium composite oxide. In this case, it is difficult to fully prevent particle damage such as cracks, collapse of the crystal structure, or changes (phase transitions) in the crystal structure inside the lithium composite oxide.
[0093] On the contrary, under the premise that the total amount of cobalt in the lithium composite oxide is the same, the slope s1 of the concentration gradient in the first concentration gradient interval is less than 2.0, which may mean that the position where the first concentration gradient interval is converted into the second concentration gradient interval is too far away from the outermost periphery of the lithium composite oxide. In this case, as the cobalt content in the surface of the lithium composite oxide decreases, it is difficult to fully prevent particle damage such as cracks, collapse of the crystal structure, or changes (phase transition) in the crystal structure in the surface of the lithium composite oxide.
[0094] Furthermore, the slope s2 of the concentration gradient of the cobalt in the lithium composite oxide in the second concentration gradient region may satisfy the following formula 2.
[0095] Formula 2: 0.2≤s2≤0.7
[0096] Under the premise that the total amount of cobalt in the lithium composite oxide is the same, the slope s2 of the concentration gradient in the second concentration gradient interval is greater than 0.7, which means that the decrease in the concentration of cobalt in the second concentration gradient interval is too large. In this case, it is difficult to fully prevent particle damage such as cracks, collapse of the crystal structure, or changes (phase transitions) in the crystal structure on the inside of the lithium composite oxide (the inside of the second concentration gradient interval).
[0097] On the contrary, under the premise that the total amount of cobalt in the lithium composite oxide is the same, the slope s2 of the concentration gradient in the second concentration gradient interval is less than 0.2, which may mean that the decrease in the concentration of cobalt in the second concentration gradient interval is too small. In this case, as the content of cobalt in the region close to the surface of the lithium composite oxide decreases, it is difficult to fully prevent particle damage such as cracks, collapse of the crystal structure, or changes (phase transition) in the crystal structure in the region close to the surface of the lithium composite oxide.
[0098] In addition, regarding the particle stability of the lithium composite oxide, it was confirmed that the slope s1 of the cobalt concentration gradient in the lithium composite oxide in the first concentration gradient range and the slope s2 of the cobalt concentration gradient in the lithium composite oxide in the second concentration gradient range had a predetermined correlation.
[0099] Specifically, when s1 and s2 satisfy the following formula 3, particle stability may be improved in the first concentration gradient region, the second concentration gradient region, and the central portion of the lithium composite oxide.
[0100] Formula 3: 1.7≤s1-s2≤3.0
[0101] In addition, the lithium composite oxide may further include a coating covering at least a portion of the interface between the primary particles and the surface of the secondary particles. In this case, the coating may contain at least one metal oxide represented by the following chemical formula 2, and preferably, at least two metal oxides.
[0102] Chemical formula 2: Li a M3 b O c
[0103] (Wherein, M3 is at least one selected from Ni, Mn, Co, Fe, Cu, Nb, Mo, Ti, Al, Cr, Zr, Zn, Na, K, Ca, Mg, Pt, Au, B, P, Eu, Sm, W, Ce, V, Ba, Ta, Sn, Hf, Ce, Gd and Nd, 0≤a≤10, 0≤b≤8, 2≤c≤13, but the case where a and b are both 0 is excluded.)
[0104] The coating layer may be in a form in which different metal oxides exist simultaneously in one layer or different metal oxides represented by the chemical formula 2 exist in separate layers.
[0105] The metal oxide represented by the chemical formula 2 may be physically and / or chemically combined with the primary particles and / or the secondary particles. Furthermore, the metal oxide may exist in a state of forming a solid solution with the primary particles and / or the secondary particles.
[0106] The metal oxide is an oxide formed by a complex of lithium and an element represented by M3 or an M3 oxide. The metal oxide may be, for example, Li a W b O c , Li a Zr b O c , Li a Ti b O c , Li a Ni b O c , Li a B b O c , Li a Co b O c , Li a Al b O c 、Co b O c 、Al b O c , W b O c 、Zr b O c 、Ti b O c or B b O c The above examples are merely provided for ease of understanding, and the metal oxides defined in the present application are not limited to the above examples.
[0107] Furthermore, the metal oxide is an oxide formed by a complexation of lithium and at least two elements represented by M3, or may further include a metal oxide formed by a complexation of lithium and at least two elements represented by M3. The metal oxide formed by a complexation of lithium and at least two elements represented by M3 may be, for example, Li a (W / Ti) b O c , Li a (W / Zr) b Oc , Li a (W / Ti / Zr) b O c , Li a (W / Ti / B) b O c etc., but not limited to these.
[0108] The different concentration gradient patterns shown by the cobalt in the above-mentioned lithium composite oxide contained in the positive electrode active material of the present application can be formed by the above-mentioned coating. That is, the different concentration gradient patterns shown by the cobalt in the above-mentioned lithium composite oxide can be realized by the concentration of cobalt present in the primary particles and / or secondary particles and the concentration of cobalt present in the metal oxide, and the above-mentioned metal oxide is present on the surface of the primary particles and / or secondary particles.
[0109] As described above, in the lithium composite oxide showing different concentration gradient patterns, particle stability in the surface and center portions can be improved, and further, the movement of ions and electrons in the center portion can be improved, thereby contributing to improving the efficiency characteristics of lithium secondary batteries.
[0110] In another embodiment, the positive electrode active material may be a bimodal positive electrode active material including a first lithium composite oxide as small particles and a second lithium composite oxide as large particles. The first lithium composite oxide and the second lithium composite oxide follow the definition of the lithium composite oxide mentioned above.
[0111] In the present application, the range of the average particle size (D50) of small particles and large particles is not particularly limited, but in order to distinguish whether any lithium composite oxide is a small particle or a large particle, the following standard range of the average particle size (D50) of small particles and large particles can be determined.
[0112] Small particles refer to lithium composite oxides having an average particle size (D50) of 7.0 μm or less, and large particles refer to lithium composite oxides having an average particle size (D50) of 7.0 μm or more. In this case, when the average particle size (D50) of the small particles is 7.0 μm, the average particle size (D50) of the large particles may be greater than 7.0 μm. Although there is no upper limit to the average particle size (D50) of the large particles, for example, the large particles may have an average particle size of 7.0 μm to 30.0 μm.
[0113] The bimodal positive active material of various embodiments of the present invention may be present in a state where the first lithium composite oxide and the second lithium composite oxide having the average particle size (D50) defined above are mixed at a weight ratio of 5:95 to 50:50.
[0114] At this time, the first lithium composite oxide may exist in a form of filling pores between the second lithium composite oxides, or may exist in a form of adhering to the surface of the second lithium composite oxide or in a form of the first lithium composite oxides being aggregated with each other.
[0115] In the positive electrode active material, when the ratio of the first lithium composite oxide is greater or less than that of the second lithium composite oxide, the compaction density of the positive electrode active material is reduced, and thus the effect of improving the energy density of the positive electrode active material per unit volume is minimal.
[0116] Lithium secondary battery
[0117] According to another embodiment of the present invention, the present invention may provide a positive electrode including a positive electrode current collector and a positive electrode active material layer formed on the positive electrode current collector. The positive electrode active material layer may include the positive electrode active material of various embodiments of the present invention. Therefore, the positive electrode active material is the same as that described previously, so for convenience, its specific description is omitted, and only the remaining structures not described above are described below.
[0118] The positive electrode current collector is not particularly limited as long as it does not induce chemical changes in the battery and has conductivity. For example, stainless steel, aluminum, nickel, titanium, calcined carbon, or the surface of aluminum or stainless steel may be treated with carbon, nickel, titanium, silver, etc. In addition, the positive electrode current collector may generally have a thickness of 3 μm to 500 μm, and fine concavoconvexities may be formed on the surface of the current collector to improve the binding force of the positive electrode active material. For example, it may be used in various forms such as a film, a sheet, a foil, a net, a porous body, a foam, and a nonwoven body.
[0119] The positive electrode active material layer may be prepared by coating a positive electrode slurry composition including the positive electrode active material, a conductive material, and optionally a binder as required, on the positive electrode current collector.
[0120] In this case, the content of the positive electrode active material can be 80 weight percent to 99 weight percent, more specifically 85 weight percent to 98.5 weight percent, relative to the total weight of the positive electrode active material layer. When the positive electrode active material is included in the above content range, excellent capacity characteristics can be shown, but it is not limited thereto.
[0121] The above-mentioned conductive materials are used to impart conductivity to the electrode. In the battery formed, as long as they do not cause chemical changes and have electronic conductivity, they can be used without limitation. As specific examples, graphite such as natural graphite or artificial graphite; carbon-based materials such as carbon black, acetylene black, Ketjen black, channel black, furnace black, lamp black, thermal black, and carbon fiber; metal powders or metal fibers such as copper, nickel, aluminum, and silver; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; or conductive polymers such as polyphenylene derivatives, etc., and one or a mixture of two or more of them can be used. The above-mentioned conductive material may be included in an amount of 0.1 weight percent to 15 weight percent relative to the total weight of the positive electrode active material layer.
[0122] The above-mentioned binder plays a role in improving the adhesion between multiple positive electrode active material particles and the bonding force between the positive electrode active material and the collector. As a specific example, polyvinylidene fluoride (PVDF), vinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinyl alcohol, polyacrylonitrile (polyacrylonitrile), carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, tetrafluoroethylene, polyethylene, polypropylene, ethylene propylene diene monomer rubber (EPDM), sulfonated ethylene propylene diene monomer rubber, styrene butadiene rubber (SBR), fluororubber or various copolymers thereof, etc., can be used. One or a mixture of two or more thereof. Relative to the total weight of the positive electrode active material layer, the above-mentioned binder may be included in an amount of 0.1 weight percent to 15 weight percent.
[0123] In addition to using the above-mentioned positive electrode active material, the above-mentioned positive electrode can be prepared according to a common positive electrode preparation method. Specifically, it can be prepared by coating a positive electrode slurry composition on a positive electrode collector and then drying and rolling it. The above-mentioned positive electrode slurry composition is prepared by dissolving or dispersing the above-mentioned positive electrode active material in a solvent and selectively dissolving or dispersing a binder and a conductive material in a solvent.
[0124] The above-mentioned solvent may be a solvent commonly used in the art, and examples thereof include dimethyl sulfoxide (DMSO), isopropyl alcohol, N-methylpyrrolidone (NMP), acetone or water, and a mixture of one or more thereof may be used. Considering the coating thickness and preparation yield of the slurry, the amount of the above-mentioned solvent used is sufficient to dissolve or disperse the above-mentioned positive electrode active material, conductive material and binder and have a viscosity that can show excellent thickness uniformity when applied to prepare the positive electrode.
[0125] Furthermore, in another embodiment, the positive electrode may be prepared by casting the positive electrode slurry composition on a separate support, and then laminating a thin film obtained by peeling the support on a positive electrode collector.
[0126] Meanwhile, according to another embodiment of the present invention, an electrochemical device comprising the positive electrode may be provided. The electrochemical device may be a battery, a capacitor, etc., and more specifically a lithium secondary battery.
[0127] Specifically, the lithium secondary battery may include a positive electrode, a negative electrode disposed opposite to the positive electrode, and a separation membrane and an electrolyte disposed between the positive electrode and the negative electrode. The positive electrode is the same as the above description, so for convenience, the specific description is omitted, and only the remaining configuration not described above is described below.
[0128] The lithium secondary battery may further include: a battery container for accommodating the electrode assembly of the positive electrode, the negative electrode and the separation membrane; and a sealing member for sealing the battery container.
[0129] The negative electrode may include a negative electrode current collector and a negative electrode active material layer located on the negative electrode current collector.
[0130] The negative electrode current collector is not particularly limited as long as it does not induce chemical changes in the battery and has high conductivity. For example, copper, stainless steel, aluminum, nickel, titanium, calcined carbon, copper or stainless steel surface treated with carbon, nickel, titanium, silver, etc., aluminum-cadmium alloy, etc. can be used. In addition, the negative electrode current collector can usually have a thickness of 3 μm to 500 μm. Similar to the positive electrode current collector, the binding force of the negative electrode active material can be strengthened by forming fine concave and convex on the surface of the collector. For example, it can be used in various forms such as a film, a sheet, a foil, a net, a porous body, a foam, and a non-woven body.
[0131] The negative electrode active material layer may be prepared by coating a negative electrode slurry composition including the negative electrode active material and a conductive material and optionally including a binder as required on the negative electrode collector.
[0132] As the negative electrode active material, a compound capable of reversibly inserting and extracting lithium can be used. Specific examples include carbon materials such as artificial graphite, natural graphite, graphitized carbon fiber, and amorphous carbon; metal compounds capable of alloying with lithium such as Si, Al, Sn, Pb, Zn, Bi, In, Mg, Ga, Cd, Si alloy, Sn alloy, or Al alloy; and SiO β(0<β<2), SnO2, vanadium oxide, lithium vanadium oxide, metal oxides capable of being doped and dedoped with lithium; or composites containing the above metal compounds and carbon materials such as Si-C composites or Sn-C composites, etc., and one or a mixture of two or more of them can be used. In addition, as the above-mentioned negative electrode active material, a metal lithium film can also be used. In addition, both low-crystalline carbon and high-crystalline carbon can be used as carbon materials. Representative low-crystalline carbons are soft carbon and hard carbon, and representative high-crystalline carbons are amorphous, plate-like, flaky, spherical or fibrous natural graphite or artificial graphite, condensed graphite (Kishgraphite), pyrolytic carbon (pyrolytic carbon), mesophase pitch-based carbon fiber (mesophase pitch based carbon fiber), mesophase carbon microbeads (meso-carbon microbeads), mesophase pitch (Mesophase pitches) and petroleum or coal tar pitch derived cokes (petroleum or coal tar pitch derived cokes) and other high-temperature sintered carbons.
[0133] Based on the total weight of the negative electrode active material layer, the negative electrode active material may be contained in an amount of 80 weight percent to 99 weight percent.
[0134] The binder is a component that helps to bind the conductive material, the active material and the current collector. Usually, based on the total weight of the negative electrode active material layer, 0.1 to 10 weight percent of the binder can be added. Examples of such binders include polyvinylidene fluoride, polyvinyl alcohol, carboxymethyl cellulose, starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, tetrafluoroethylene, polyethylene, polypropylene, ethylene propylene diene monomer rubber, sulfonated ethylene propylene diene monomer rubber, styrene butadiene rubber, nitrile rubber, fluororubber, and various copolymers thereof.
[0135] The conductive material is a component used to further improve the conductivity of the negative electrode active material. Based on the total weight of the negative electrode active material layer, the conductive material can be added in an amount of 10 weight percent or less, preferably, 5 weight percent or less. There is no particular limitation on the conductive material as long as it does not induce chemical changes in the corresponding battery and has conductivity. For example, graphite such as natural graphite or artificial graphite; carbon black such as acetylene black, ketjen black, channel black, furnace black, lamp black, thermal black; conductive fibers such as carbon fibers or metal fibers; metal powders such as carbon fluoride, aluminum, and nickel powder; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; conductive materials such as polyphenylene derivatives, etc. can be used.
[0136] In one embodiment, the negative electrode active material layer may be prepared by coating a negative electrode slurry composition on a negative electrode collector and drying it, wherein the negative electrode slurry composition is prepared by dissolving or dispersing the negative electrode active material in a solvent and selectively dissolving or dispersing a binder and a conductive material in a solvent, or by casting the negative electrode slurry composition on a separate support and laminating a thin film obtained by peeling off the support on the negative electrode collector.
[0137] Furthermore, in another embodiment, the negative electrode active material layer can also be prepared by coating a negative electrode slurry composition on a negative electrode collector and drying it. The negative electrode slurry composition is prepared by dissolving or dispersing the negative electrode active material in a solvent and selectively dissolving or dispersing a binder and a conductive material in a solvent. Alternatively, the negative electrode slurry composition is poured on a separate support and then a thin film obtained by peeling off the support is laminated on the negative electrode collector.
[0138] In addition, in the above-mentioned lithium secondary battery, the separation membrane is used to separate the negative electrode and the positive electrode and provide a mobile channel for lithium ions. As long as the separation membrane commonly used in the lithium secondary battery, it can be used without restriction, especially, preferably, for the ion movement of the electrolyte, the impedance is low and has excellent electrolyte moisture-containing capacity. Specifically, a porous polymer film can be used, for example, a porous polymer film prepared by polyolefin polymers such as ethylene homopolymers, propylene homopolymers, ethylene / butene copolymers, ethylene / hexene copolymers and ethylene / methacrylate copolymers or their two or more layers of stacked structures. In addition, a common porous non-woven fabric can also be used, for example, a non-woven fabric made of high melting point glass fiber, polyethylene terephthalate fiber, etc. In addition, in order to ensure heat resistance or mechanical strength, a separation membrane coated with a ceramic component and a polymer substance can also be used, which can be selectively used with a single layer or multilayer structure.
[0139] Furthermore, examples of the electrolyte used in the present invention include, but are not limited to, organic liquid electrolytes, inorganic liquid electrolytes, solid polymer electrolytes, gel polymer electrolytes, solid inorganic electrolytes, and molten inorganic electrolytes that can be used in preparing lithium secondary batteries.
[0140] Specifically, the electrolyte may include an organic solvent and a lithium salt.
[0141] As the above-mentioned organic solvent, any organic solvent that can act as a medium for the movement of ions involved in the electrochemical reaction of the battery can be used without limitation. Specifically, as the above-mentioned organic solvent, ester solvents such as methylacetate, ethylacetate, γ-butyrolactone, ε-caprolactone, etc.; ether solvents such as dibutyl ether or tetrahydrofuran; ketone solvents such as cyclohexanone; aromatic hydrocarbon solvents such as benzene and fluorobenzene; dimethyl carbonate (DMC), diethyl carbonate (DEC), methylethyl carbonate (MEC), ethylmethyl carbonate (EMC), ethylene carbonate (EC), propylene carbonate (EPC), etc. can be used. carbonate, PC) and other carbonate solvents; alcohol solvents such as ethanol and isopropanol; nitriles such as R-CN (R is a straight-chain, branched or cyclic hydrocarbon group with 2 to 20 carbon atoms, which may contain a double-bonded aromatic ring or an ether bond); amides such as dimethylformamide; dioxolanes such as 1,3-dioxolane; or sulfolane, etc. Among them, carbonate solvents are preferred, and more preferably, a mixture of cyclic carbonates (such as ethylene carbonate or propylene carbonate) with high ionic conductivity and high dielectric constant that can improve the charge and discharge performance of the battery, and low-viscosity linear carbonate compounds (such as ethyl methyl carbonate, dimethyl carbonate or diethyl carbonate, etc.). In this case, when the cyclic carbonate and the chain carbonate are mixed in a volume ratio of about 1:1 to about 1:9 for use, excellent electrolyte performance can be shown.
[0142] The above-mentioned lithium salt can use compounds that can provide lithium ions used in lithium secondary batteries without limitation. Specifically, the above-mentioned lithium salt can use LiPF6, LiClO4, LiAsF6, LiBF4, LiSbF6, LiAlO4, LiAlCl4, LiCF3SO3, LiC4F9SO3, LiN(C2F5SO3)2, LiN(C2F5SO2)2, LiN(CF3SO2)2, LiCl, LiI or LiB(C2O4)2, etc. Preferably, the concentration of the above-mentioned lithium salt is used in the range of 0.1M to 2.0M. If the concentration of the lithium salt is included in the above range, the electrolyte has appropriate conductivity and viscosity, and therefore, excellent electrolyte performance can be shown, and lithium ions can be effectively moved.
[0143] In addition to the above electrolyte components, the electrolyte may also include one or more additives such as halogenated alkylene carbonate compounds such as bis(fluoroethylene carbonate), pyridine, triethyl phosphite, triethanolamine, cyclic ether, ethylenediamine, n-glyme, hexaphosphoric acid triamide, nitrobenzene derivatives, sulfur, quinone imine dyes, N-substituted oxazolidinones, N,N-substituted imidazolidines, ethylene glycol dialkyl ethers, ammonium salts, pyrrole, 2-methoxyethanol or aluminum chloride, etc., for the purpose of improving the life characteristics of the battery, inhibiting the reduction of the battery capacity, and increasing the discharge capacity of the battery. In this case, the above additives may be included in an amount of 0.1% by weight to 5% by weight relative to the total weight of the electrolyte.
[0144] As described above, the lithium secondary battery containing the positive electrode active material of the present invention stably shows excellent discharge capacity, output characteristics and life characteristics, and can therefore be used in portable devices such as mobile phones, notebook computers, digital cameras, and electric vehicles such as hybrid electric vehicles (HEV).
[0145] The shape of the lithium secondary battery of the present invention is not particularly limited, and may be cylindrical, prismatic, pouch, or coin-shaped using a can, etc. Also, preferably, the lithium secondary battery can be used not only as a battery cell used as a power source for small devices, but also as a unit battery of a medium or large battery module including a plurality of battery cells.
[0146] According to still another embodiment of the present invention, a battery module including the lithium secondary battery as a unit cell and / or a battery pack including the same may be provided.
[0147] The battery module or the battery pack can be used as a power tool; an electric vehicle including an electric vehicle (EV), a hybrid electric vehicle and a plug-in hybrid electric vehicle (PHEV); or a power source for one or more medium or large devices in a power storage system.
[0148] Hereinafter, the present invention will be described in more detail by way of examples, but these examples are only for illustrating the present invention and should not be construed as limiting the scope of the present invention to these examples.
[0149] Preparation Example 1. Preparation of positive electrode active material
[0150] (1) Embodiment 1
[0151] (a) A NiCoAl(OH)2 hydroxide precursor (Ni:Co:Al=95:4:1 (at%)) was synthesized by a known co-precipitation method using nickel sulfate, cobalt sulfate and aluminum sulfate. The synthesized hydroxide precursor was heated to 400°C at a heating rate of 2°C per minute and then calcined at 400°C for 6 hours to convert it into an oxide precursor.
[0152] (b) After mixing the above-mentioned oxide precursor prepared in the above-mentioned step (a) with LiOH (Li / (Ni+Co+Al) molar ratio = 1.05), maintaining an O2 atmosphere in a sintering furnace, heating to 800°C at a heating rate of 2°C per minute, and heat treating at 800°C for 12 hours to obtain a lithium composite oxide.
[0153] (c) A 3.0 mol% aqueous solution of cobalt sulfate was prepared based on the concentration of transition metals in the lithium composite oxide, and the solution was added to the lithium composite oxide while stirring for 1 hour to prepare a mixture. The mixture was dehydrated and then dried at 120° C. for 12 hours to prepare a dried product.
[0154] (d) After mixing the dried product with B2O3 (B / (Ni+Co+Al) molar percentage = 0.3), the mixture was heated to 700°C at a rate of 2°C per minute in a sintering furnace while maintaining an O2 atmosphere. The mixture was then heat treated at 700°C for 12 hours to obtain a Li1Ni 0.9179 Co 0.0691 Al 0.0100 B 0.0030 The composition of the lithium composite oxide was confirmed by ICP analysis.
[0155] (2) Embodiment 2
[0156] (a) A NiCoAl(OH)2 hydroxide precursor (Ni:Co:Al=95:4:1 (at%)) was synthesized by a known coprecipitation method using nickel sulfate, cobalt sulfate and aluminum sulfate. The synthesized hydroxide precursor was heated to 400°C at a heating rate of 2°C per minute and then calcined at 400°C for 6 hours to convert it into an oxide precursor.
[0157] (b) The oxide precursor prepared in the above step (a) is mixed with LiOH (Li / (Ni+Co+Al) molar ratio = 1.05) and B2O3 (Li / (Ni+Co+Al) molar percentage = 0.2), and then the mixture is heated to 800°C at a heating rate of 2°C per minute in a sintering furnace to obtain a lithium composite oxide.
[0158] (c) A 3.0 mol% aqueous solution of cobalt sulfate was prepared based on the concentration of transition metals in the lithium composite oxide, and the solution was added to the lithium composite oxide while stirring for 1 hour to prepare a mixture. The mixture was dehydrated and then dried at 120° C. for 12 hours to prepare a dried product.
[0159] (d) After mixing the dried product with B2O3 ((B / (Ni+Co+Al) molar percentage = 0.3), the mixture was heated to 700°C at a rate of 2°C per minute in a sintering furnace, and then heat treated at 700°C for 12 hours to obtain Li1Ni 0.9161 Co 0.0689 Al 0.0100 B 0.0050 The composition of the lithium composite oxide was confirmed by ICP analysis.
[0160] (3) Embodiment 3
[0161] In step (d), the dried product was mixed with B2O3 (B / (Ni+Co+Al) molar percentage = 0.5) and then heat treated. A lithium composite oxide was obtained by the same method as in Example 1. The results of ICP analysis confirmed that the obtained lithium composite oxide had Li1Ni 0.9161 Co 0.0689 Al 0.0100 B 0.0050 O2 Composition The composition of the lithium composite oxide was confirmed by ICP analysis.
[0162] (4) Embodiment 4
[0163] In step (d), the dried product was mixed with B2O3 (B / (Ni+Co+Al) molar percentage = 0.3) and ZrO2 (Zr / (Ni+Co+Al) molar percentage = 0.2) and then heat treated. A lithium composite oxide was obtained by the same method as in Example 3. The results of ICP analysis confirmed that the obtained lithium composite oxide had Li1Ni 0.9161 Co 0.0689 Al 0.010 B0.0030 Zr 0.0020 O2 Composition The composition of the lithium composite oxide was confirmed by ICP analysis.
[0164] ( 5) Embodiment 5
[0165] In step (b), the dried product was mixed with B2O3 (B / (Ni+Co+Al) molar percentage = 0.3) and TiO2 (Ti / (Ni+Co+Al) molar percentage = 0.2) and then calcined. A lithium composite oxide was obtained by the same method as in Example 1. The results of ICP analysis confirmed that the obtained lithium composite oxide had Li1Ni 0.9161 Co 0.0689 Al 0.010 B 0.0030 Ti 0.0020 O2 Composition The composition of the lithium composite oxide was confirmed by ICP analysis.
[0166] (6) Embodiment 6
[0167] In step (b), the dried product was mixed with B2O3 (B / (Ni+Co+Al) molar percentage = 0.3) and MgO (Mg / (Ni+Co+Al) molar percentage = 0.2) and then calcined. A lithium composite oxide was obtained by the same method as in Example 1. The results of ICP analysis confirmed that the obtained lithium composite oxide had Li1Ni 0.9161 Co 0.0689 Al 0.010 B 0.0030 Mg 0.0020 O2 Composition The composition of the lithium composite oxide was confirmed by ICP analysis.
[0168] (7) Comparative Example 1
[0169] (a) A NiCoAl(OH)2 hydroxide precursor (Ni:Co:Al=95:4:1 (at%)) was synthesized by a known coprecipitation method using nickel sulfate, cobalt sulfate and aluminum sulfate. The synthesized hydroxide precursor was heated to 400°C at a heating rate of 2°C per minute and then calcined at 400°C for 6 hours to convert it into an oxide precursor.
[0170] (b) The oxide precursor prepared in the above step (a) is mixed with LiOH (Li / (Ni+Co+Al) molar ratio = 1.05) and B2O3 (B / (Ni+Co+Al) molar percentage = 0.3), and then the mixture is heated to 800°C at a rate of 2°C per minute in a sintering furnace while maintaining an O2 atmosphere. The mixture is then heat treated at 800°C for 12 hours to obtain a lithium composite oxide.
[0171] (c) A 3.0 mol% aqueous solution of cobalt sulfate was prepared based on the concentration of transition metals in the lithium composite oxide, and the solution was added to the lithium composite oxide while stirring for 1 hour to prepare a mixture. The mixture was dehydrated and then dried at 120° C. for 12 hours to prepare a dried product.
[0172] (d) The dried product was heated to 700°C at a rate of 2°C per minute in a sintering furnace while maintaining an O2 atmosphere, and then heat treated at 700°C for 12 hours to obtain a Li1Ni 0.9179 Co 0.0691 Al 0.0100 B 0.0030 The composition of the lithium composite oxide was confirmed by ICP analysis.
[0173] (8) Comparative Example 2
[0174] In step (d), the dried product was mixed with B2O3 (B / (Ni+Co+Al) molar percentage = 0.8) and then calcined. A lithium composite oxide was obtained by the same method as in Example 2. The results of ICP analysis confirmed that the obtained lithium composite oxide had Li1Ni 0.9113 Co 0.0687 Al 0.0100 B 0.0100 O2 Composition The composition of the lithium composite oxide was confirmed by ICP analysis.
[0175] (9) Comparative Example 3
[0176] In step (d), the dried product was mixed with B2O3 (B / (Ni+Co+Al) molar percentage = 1.0) and then calcined. A lithium composite oxide was obtained by the same method as in Example 1. The results of ICP analysis confirmed that the obtained lithium composite oxide had Li1Ni 0.9113 Co 0.0687 Al 0.0100 B 0.0100 O2 Composition The composition of the lithium composite oxide was confirmed by ICP analysis.
[0177] (10) Comparative Example 4
[0178] (a) A NiCoAl(OH)2 hydroxide precursor (Ni:Co:Al=95:4:1 (at%)) was synthesized by a known coprecipitation method using nickel sulfate, cobalt sulfate and aluminum sulfate. The synthesized hydroxide precursor was heated to 400°C at a heating rate of 2°C per minute and then calcined at 400°C for 6 hours to convert it into an oxide precursor.
[0179] (b) After mixing the above-mentioned oxide precursor prepared in the above-mentioned step (a) with LiOH (Li / (Ni+Co+Al) molar ratio = 1.05), maintaining an O2 atmosphere in a sintering furnace, heating to 800°C at a heating rate of 2°C per minute, and then heat treating at 800°C for 12 hours to obtain a lithium composite oxide.
[0180] (c) The lithium composite oxide was heated to 700°C at a rate of 2°C per minute in a sintering furnace while maintaining an O2 atmosphere, and then heat treated at 700°C for 12 hours to obtain a Li1Ni 0.950 Co 0.040 Al 0.010 The composition of the lithium composite oxide was confirmed by ICP analysis.
[0181] Preparation Example 2. Preparation of lithium secondary battery
[0182] A positive electrode slurry was prepared by dispersing 92 weight percent of each positive electrode active material prepared according to Preparation Example 1, 4 weight percent of artificial graphite, and 4 weight percent of polyvinylidene fluoride binder in 30 g of N-methylpyrrolidone. The positive electrode slurry was evenly coated on an aluminum film with a thickness of 15 μm and vacuum dried at a temperature of 135° C., thereby preparing a positive electrode for a lithium secondary battery.
[0183] Relative to the above-mentioned positive electrode, lithium foil was used as a counter electrode, a porous polyethylene film (Celgard 2300, thickness: 25 μm) was used as a separation membrane, and an electrolyte solution containing LiPF6 at a concentration of 1.15 M in a solvent of ethylene carbonate and ethyl methyl carbonate mixed in a volume ratio of 3:7 was used to prepare a button battery.
[0184] Experimental Example 1. Energy Analysis of Positive Electrode Active Material - Energy Dispersive X-ray Spectroscopy
[0185] Energy analysis-energy dispersive X-ray spectroscopy was performed to measure the cobalt content in the lithium composite oxide contained in the positive electrode active material prepared according to Preparation Example 1. When performing energy analysis-energy dispersive X-ray spectroscopy, after screening the lithium composite oxide contained in the positive electrode active material prepared according to Preparation Example 1, the acceleration voltage of the electron beam irradiated to the surface of the screened lithium composite oxide was changed from 1 kV to 30 kV (1 kV, 3 kV, 5 kV, 7.5 kV, 10 kV, 12.5 kV, 15 kV, 22.5 kV, 30 kV), and the cumulative concentration (at%) of cobalt up to a specific depth penetrated by the electron beam of each acceleration voltage was analyzed.
[0186] The region where the acceleration voltage of the electron beam irradiated to the surface of the lithium composite oxide is 1 kV to 10 kV is set as the first concentration gradient region, and the region where the acceleration voltage is 10 kV to 30 kV is set as the second concentration gradient region. Furthermore, the slope of the cobalt concentration gradient in the first concentration gradient region is set as s1, and the slope of the cobalt concentration gradient in the second concentration gradient region is set as s2.
[0187] In s1 and s2 representing the slope of the cobalt concentration gradient, the y-axis is set to the change in cobalt concentration (Δat%) and the x-axis is set to the change in EDS acceleration voltage (ΔkV%), and the calculation is performed using the average value calculated by summing up the slopes of each measurement area.
[0188] The energy analysis-energy dispersive X-ray spectroscopy analysis results of the lithium composite oxide contained in the positive electrode active material prepared in Preparation Example 1 are shown in Tables 1 and 2 below.
[0189] Table 1
[0190]
[0191]
[0192] Table 2
[0193] Classification s1 s2 s1-s2 Example 1 2.86 0.29 2.57 Example 2 2.88 0.34 2.54 Example 3 2.81 0.43 2.38 Example 4 2.31 0.59 1.72 Example 5 2.35 0.44 1.91 Example 6 2.78 0.52 2.26 Comparative Example 1 1.89 0.28 1.61 Comparative Example 2 3.66 0.46 3.20 Comparative Example 3 5.38 0.78 4.60 Comparative Example 4 1.00 0.83 0.17
[0194] Referring to the results in Tables 1 and 2 above, a concentration gradient is formed in which the concentration of cobalt decreases from the surface portion toward the center portion of the lithium composite oxide contained in the positive electrode active material according to Examples 1 to 6. At this time, the region where the acceleration voltage of the electron beam irradiated to the surface of the above lithium composite oxide is 1 kV to 10 kV is set as the first concentration gradient interval, and it can be confirmed that there is a significant difference between the slopes of the concentration gradients in the second concentration gradient interval where the acceleration voltage is 10 kV to 30 kV.
[0195] On the contrary, in the case of the lithium composite oxide contained in the positive electrode active material according to Comparative Example 4, a concentration gradient is formed in which the concentration of cobalt decreases from the surface portion toward the center portion, but the region where the acceleration voltage of the electron beam irradiated to the surface of the above-mentioned lithium composite oxide is 1 kV to 10 kV is set as the first concentration gradient interval, and it can be confirmed that there is no significant difference between the slopes of the concentration gradients in the second concentration gradient interval in the region where the acceleration voltage is 10 kV to 30 kV.
[0196] Experimental example 2. lithium Evaluation of electrochemical characteristics of secondary batteries
[0197] For the lithium secondary battery (button battery) prepared in Preparation Example 2, a charge and discharge experiment was performed using an electrochemical analyzer (Toyo, Toscat-3100) at a temperature of 25°C, a voltage range of 3.0V to 4.25V, and a discharge rate of 0.2C to measure the charge and discharge capacity.
[0198] Furthermore, for the same lithium secondary battery, after charging / discharging 50 times at 1C / 1C at a temperature of 25°C and a driving voltage range of 3.0V to 4.25V, the ratio of the discharge capacity at the 50th cycle to the initial capacity (cycle capacity retention) was measured.
[0199] The above measurement results are shown in Table 3 below.
[0200] Table 3
[0201]
[0202] Experimental Example 3. Stability Evaluation of Positive Electrode Active Material and Lithium Secondary Battery
[0203] (1) Crack area of positive electrode active material after life
[0204] For the lithium secondary battery (button battery) prepared in Preparation Example 2, after charging / discharging 50 times at 1C / 1C under the condition of 25°C and a driving voltage range of 3.0V to 4.25V, the positive electrode was separated, the positive electrode active material was recovered from the separated positive electrode, and a cross-sectional scanning electron microscope (SEM) image was taken.
[0205] In order to quantify the crack area in the cross-sectional scanning electron microscope image, the peripheries of multiple particles confirmed from the (binary) cross-sectional scanning electron microscope image are set, the dark areas in the above peripheries are regarded as cracks, and the area ratio of the dark areas in the overall area of the above peripheries is defined as the crack occurrence rate (%).
[0206] Table 4 below shows the crack occurrence rates measured by the above-mentioned method.
[0207] Table 4
[0208] Classification Crack incidence (%) Example 1 11.9 Example 2 12.0 Example 3 12.5 Example 4 11.5 Example 5 13.0 Example 6 12.7 Comparative Example 1 30.0 Comparative Example 2 27.9 Comparative Example 3 31.9 Comparative Example 4 32.8
[0209] Referring to the results in Table 4, it can be confirmed that the positive electrode active materials of Examples 1 to 6 have a lower crack occurrence rate after the life of the lithium secondary battery than the positive electrode active materials of Comparative Examples 1 to 4.
[0210] (2) Measurement of gas generation from lithium secondary batteries
[0211] The lithium secondary battery prepared in Preparation Example 2 was charged to 4.25 V at a static current of 0.2 C and then stored at 60° C. for 14 days to measure the volume change of the lithium secondary battery caused by gas generation in the lithium secondary battery. The volume change measurement results are shown in Table 5 below.
[0212] Table 5
[0213] Classification <![CDATA[Gas generation amount (Δcm 3 )]]> Example 1 0.16 Example 2 0.23 Example 3 0.27 Example 4 0.11 Example 5 0.19 Example 6 0.21 Comparative Example 1 0.74 Comparative Example 2 0.71 Comparative Example 3 0.51 Comparative Example 4 0.77
[0214] With repeated charge and discharge, cracks are generated in the positive electrode active material, and through the cracks, the positive electrode active material and the electrolyte undergo a side reaction, thereby increasing the possibility of gas generation. Referring to the results of Table 6 above, it can be confirmed that the volume change of the lithium secondary battery using the positive electrode active material of Examples 1 to 6 is less than the volume change of the lithium secondary battery using the positive electrode active material of Comparative Examples 1 to 4.
Claims
1. A positive electrode active material comprising a lithium composite oxide containing at least nickel and cobalt, characterized in that: The cobalt in the lithium composite oxide has a concentration gradient that decreases from the surface portion toward the center portion of the lithium composite oxide. The cobalt concentration gradient has at least different slopes, and the signs of the different slopes are the same. When energy analysis-energy dispersive X-ray spectroscopy is performed, there is an inflection point of the change in the slope of the concentration gradient of the cobalt in the lithium composite oxide in the region of an accelerating voltage of 7.5 kV to 12.5 kV, and in the energy analysis-energy dispersive X-ray spectroscopy, the cumulative concentration of the cobalt from the surface of the lithium composite oxide to the depth into which the electron beam penetrates is measured using an electron beam irradiated with an accelerating voltage increasing from 1 kV to 30 kV on the surface of the lithium composite oxide, When the slope of the cobalt concentration gradient in the lithium composite oxide in the region of the accelerating voltage of 1 kV to 10 kV is set to s1 and the slope of the cobalt concentration gradient in the lithium composite oxide in the region of the accelerating voltage of 10 kV to 30 kV is set to s2, s1 and s2 satisfy the following equations 1 and 3: Formula 1: 2.0≤s1≤3.6, Formula 3: 1.7≤s1-s2≤3.
0.
2. The positive electrode active material according to claim 1, characterized in that The lithium composite oxide is a secondary particle formed by the aggregation of a plurality of primary particles. The cobalt in the secondary particle has a concentration gradient that decreases from the surface portion toward the center portion of the secondary particle. When energy analysis-energy dispersive X-ray spectroscopy is performed, there is an inflection point where the slope of the concentration gradient of cobalt in the above-mentioned secondary particles changes in the region of acceleration voltage of 7.5kV to 12.5kV. In the energy analysis-energy dispersive X-ray spectroscopy, for the surface of the above-mentioned secondary particles, the cumulative concentration of the above-mentioned cobalt from the surface of the above-mentioned secondary particles to the depth penetrated by the above-mentioned electron beam is measured using an electron beam irradiated with an acceleration voltage increased from 1kV to 30kV.
3. The positive electrode active material according to claim 1, characterized in that When the slope of the concentration gradient of the cobalt in the lithium composite oxide in the region of the accelerating voltage of 10 kV to 30 kV is set to s2, The above s2 satisfies the following formula 2: Formula 2: 0.2≤s2≤0.
7.
4. The positive electrode active material according to claim 1, characterized in that The lithium composite oxide is represented by the following chemical formula 1: Chemical formula 1: Li w Ni 1-(x+y+z+z') Co x M1 y M2 z B z' O2 in, M1 is at least one selected from Mn and Al, M2 is at least one selected from P, Sr, Ba, Ti, Zr, Mn, Al, W, Ce, Hf, Ta, Cr, F, Mg, V, Fe, Zn, Si, Y, Ga, Sn, Mo, Ge, Nd, Gd and Cu, M1 and M2 are different from each other. 0.5≤w≤1.5,0 <x≤0.50,0≤y≤0.20,0≤z≤0.20,0≤z'≤0.20。 5. The positive electrode active material according to claim 2, characterized in that The lithium composite oxide further includes a coating layer covering at least a portion of the interface between the primary particles and the surface of the secondary particles. The coating contains at least one metal oxide represented by the following chemical formula 2: Chemical formula 2: Li a M3 b O c in, M3 is at least one selected from Ni, Mn, Co, Fe, Cu, Nb, Mo, Ti, Al, Cr, Zr, Zn, Na, K, Ca, Mg, Pt, Au, B, P, Eu, Sm, W, Ce, V, Ba, Ta, Sn, Hf, Gd and Nd, 0≤a≤10, 0≤b≤8, 2≤c≤13, but the case where a and b are both 0 is excluded.
6. A positive electrode, characterized in that The positive electrode active material comprises the positive electrode active material according to any one of claims 1 to 5.
7. A lithium secondary battery, characterized in that: The positive electrode according to claim 6 is used.
Citation Information
Patent Citations
Cathode active material for secondary battery, preparation method therefor, and secondary battery comprising same
CN107408667A
Positive electrode active material for secondary battery, positive electrode, for secondary battery, comprising same, and secondary battery
CN107949938A